Vampires, bones and treacle scones ebook - Dunnett, Kaitlyn (Liss MacCrimmon Mystery., 2013)
After a murder in a Maine mansion, an amateur sleuth must take a bite out of crime: "Spooky . . . Cozy fans are in for a Halloween treat." — Publishers Weekly Liss MacCrimmon's Scottish Emporium is thrilled to be organizing Moosetookalok, Maine's Halloween fundraiser. But the abandoned Chadwick mansion might be too perfect a setting for a creepy old haunted house, especially when a very real-looking body with puncture marks on the neck is added to the decorations. Asking who kilt the deceased brings up everyone from the undead to real estate agents to horror writers. But Liss had better watch her back, because the killer is much closer than she thinks! "A solid addition to this charming series." — RT Book Reviews "Gives readers a chance to catch up with old friends and meet new ones." — Kirkus